Correlation in the heart rate data - Ulbikas, J.; Čenys, A.; Žemaitytė, D.; Varoneckas, G. (Nonlinear Analysis: Modelling and Control, 1998)
Variety of methods of nonlinear dynamics have been used for possibility of an analysis of time series in experimental physiology. Dynamical nature of experimental data was checked using specific methods. Statistical properties of the heart rate have been investigated. Correlation between of cardiovascular function and statistical properties of both, heart rate and stroke volume, have been analyzed. Possibility to use a data from correlations in heart rate for monitoring of cardiovascular function was discussed.